High-performance, low-power resonant clocking - Guthaus, Matthew R.; Taskin, Baris (Proceedings of the International Conference on Computer-Aided Design, 2012)
Clock distribution networks consume a significant portion of on-chip power. Traditional buffered clock distribution power is limited by frequency, capacitance, and activity rates. Resonant clock distributions can reduce this power by "recycling" energy on-chip and reducing the overall clock power. This tutorial introduces recent techniques for distributed-LC, traveling wave, and standing wave resonant clock distributions. In particular, the tutorial discusses the recent developments and open research problems. The tutorial covers both circuits, computer-aided design algorithms and methodologies for resonant clocking.